Positive electrode active material and lithium secondary battery including same

By using dopants and increasing the calcination temperature during the calcination process of the positive electrode active substance of the lithium secondary battery, the growth of primary particles and the crystallinity is suppressed, and the stability reduction and gas generation problems caused by nickel-based lithium composite oxide are solved, and the maintenance of electrochemical performance and the improvement of life are achieved.

CN119905543APending Publication Date: 2025-04-29ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411432190.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-26
Filing Date
2024-10-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In lithium secondary batteries, the use of nickel-based lithium composite oxides leads to an increase in cation mixing, reducing stability, and causing gas generation and swelling.

Method used

By using dopants that hinder primary particles' growth during the calcination process of the positive electrode active material and increasing the calcination temperature, the overgrowth of primary particles is inhibited and its crystallinity is improved, thereby reducing crystal defects.

Benefits of technology

While maintaining the electrochemical performance of lithium secondary batteries, it prevents and/or slows down the gas generation and swelling caused by the positive electrode active substance, and improves the life performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905543A_ABST
    Figure CN119905543A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a lithium secondary battery comprising the same, and more specifically, to a lithium secondary battery using a lithium composite oxide as a positive electrode active material, which maintains the electrochemical performance of the lithium secondary battery by suppressing the overgrowth of primary particles and improving the crystallinity of the primary particles. And a lithium secondary battery including the positive electrode active material. The positive electrode active material can prevent and / or alleviate gas generation and swelling phenomena in the lithium secondary battery caused by the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more specifically, to a positive electrode active material and a lithium secondary battery including the same, which can maintain the electrochemical performance of a lithium secondary battery using the above-mentioned lithium composite oxide as a positive electrode active material by suppressing excessive growth of primary particles and improving the crystallinity of primary particles, while being able to prevent and / or alleviate gas generation and swelling in the lithium secondary battery caused by the above-mentioned positive electrode active material. Background Art

[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.

[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as positive electrode active materials for lithium secondary batteries, and for example, composite oxides such as LiCoO2, LiMn2O4, LiNiO2, and LiMnO2 are currently under study.

[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent life performance and charge and discharge efficiency, but has the disadvantage of limited price competitiveness because cobalt used as a raw material is expensive.

[0006] Lithium manganese-based oxides such as LiMnO2 and LiMn2O4 have the advantages of excellent thermal stability and low price, but have the problems of small capacity and poor high temperature characteristics. In addition, LiNiO2-based positive electrode active materials have battery characteristics of high discharge capacity, but due to the active cation mixing between lithium and nickel, it is not only difficult to synthesize, but also has the problem that the rate performance and life performance of the synthesized positive electrode active materials are very low.

[0007] Accordingly, in order to improve the low rate performance and life performance while maintaining the high reversible capacity of LiNiO2, the so-called ternary type, the so-called NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) ternary type or NCMA (Ni-Co-Mn-Al) quaternary type lithium composite oxides such as ternary type in which a part of nickel is replaced by cobalt, manganese and / or aluminum have been developed. Since the lower the nickel content in the ternary or quaternary lithium composite oxide as described above, the lower the reversible capacity, therefore, recently, active research has been conducted to increase the nickel content in the lithium composite oxide.

[0008] However, as the nickel content in the lithium composite oxide increases, the cation mixing phenomenon in the crystal structure also increases, resulting in a decrease in stability or an increase in the content of unreacted lithium impurities such as LiOH and Li2CO3 on the surface.

[0009] As the crystallinity changes such as the increase of cation mixing in the crystal structure of the lithium composite oxide increase or the content of lithium impurities remaining on the surface of the lithium composite oxide increases, the gas generation and swelling phenomenon in the lithium secondary battery using the lithium composite oxide as the positive electrode active material may be aggravated. As the content of lithium impurities remaining on the surface of the lithium composite oxide increases, when the paste for forming the positive electrode active material layer is prepared using the lithium composite oxide, there is a problem of gelation of the paste composition due to lithium impurities.

[0010] In order to solve the gas generation problem caused by the lithium impurities remaining on the surface of the above-mentioned lithium composite oxide, there is a method proposed to form a coating derived from a metal oxide or a coating derived from a polymer by reacting the lithium impurities existing on the surface of the above-mentioned lithium composite oxide with a coating raw material. However, if a coating is formed on the surface of the above-mentioned lithium composite oxide, the surface resistance characteristics of the above-mentioned lithium composite oxide may be changed, thereby reducing the electrochemical performance such as the charge and discharge capacity and / or rate performance of the lithium secondary battery using the above-mentioned lithium composite oxide as the positive electrode active material.

[0011] Therefore, it is necessary to develop a positive electrode active material that can maintain the electrochemical performance of a lithium secondary battery using the above-mentioned lithium composite oxide as a positive electrode active material, and can prevent and / or mitigate the gas generation and swelling phenomenon in the lithium secondary battery caused by the above-mentioned positive electrode active material. Summary of the invention

[0012] Technical issues

[0013] In the lithium secondary battery market, while the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, the demand for positive electrode active materials used in lithium secondary batteries is also changing.

[0014] For example, in the prior art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, but recently, the use of nickel-based lithium composite oxides having a larger energy capacity per unit weight than LFP is expanding (of course, relatively cheap LFP is still used at present to reduce costs).

[0015] In addition, nickel-based lithium composite oxides, which are recently mainly used as positive electrode active materials for high-capacity lithium secondary batteries, generally have a ternary type composition such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or a quaternary type composition such as NCMA (Ni-Co-Mn-Al).

[0016] As mentioned above, in order to achieve the high capacity of this ternary or quaternary nickel-based lithium composite oxide, it is necessary to increase the nickel content in the above-mentioned lithium composite oxide. However, as the nickel content in the above-mentioned lithium composite oxide increases, changes in crystallinity such as increased cation mixing in the crystal structure of the above-mentioned lithium composite oxide increase, or the content of lithium impurities remaining on the surface of the above-mentioned lithium composite oxide may increase.

[0017] Therefore, the object of the present invention is to provide a positive electrode active material, which inhibits the excessive growth of primary particles and improves the crystallinity of primary particles by using a dopant that hinders the growth of primary particles in a lithium composite oxide during the calcination process of the positive electrode active material and increasing the calcination temperature, thereby preventing and / or slowing down the gas generation and swelling phenomenon in the lithium secondary battery caused by the above-mentioned positive electrode active material while maintaining the electrochemical performance of the lithium secondary battery using the above-mentioned lithium composite oxide as the positive electrode active material.

[0018] In addition, an object of the present invention is to provide a positive electrode active material which can prevent and / or mitigate the generation of cracks due to strain caused by random volume contraction / expansion of the primary particles during charge and discharge by reducing crystal defects in the crystal structure of the primary particles constituting the above-mentioned lithium composite oxide.

[0019] In addition, another object of the present invention is to provide a lithium secondary battery using the positive electrode active material defined herein.

[0020] The purpose of the present invention is not limited to the purpose mentioned above, and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.

[0021] Solutions to the problem

[0022] According to one aspect of the present invention, there is provided a positive electrode active material including primary particles capable of inserting and extracting lithium ions and secondary particles formed by aggregating the primary particles.

[0023] The secondary particles may include at least one selected from nickel, cobalt, manganese and aluminum. Preferably, the secondary particles include nickel.

[0024] In addition, the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the primary particle may slightly vary depending on the charge state of the positive electrode active material and the composition of the positive electrode active material (for example, the molar fraction of nickel).

[0025] For example, in the above-mentioned positive electrode active material, the molar fraction of nickel relative to all elements except lithium can be greater than 70%, and when charged to 4.3V, the maximum value (d1) of the interplanar spacing of the (003) planes in the crystal structure of the above-mentioned primary particles, that is, the d-spacing, can be less than 0.4794nm, and the minimum value (d2) of the interplanar spacing of the (003) planes in the crystal structure of the above-mentioned primary particles present in the above-mentioned secondary particles, that is, the d-spacing, can be greater than 0.456nm.

[0026] As described above, the maximum value (d1) and / or minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the primary particle may vary slightly according to the charge state of the positive electrode active material and the composition of the positive electrode active material (e.g., the molar fraction of nickel). However, the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the primary particle is not significantly affected by the charge state of the positive electrode active material or the change in the molar fraction of nickel in the positive electrode active material, and therefore can be used as an indicator of crystal defects in the crystal structure of the primary particle.

[0027] Therefore, the smaller the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the above-mentioned primary particle crystal structure, the more the crystal defects in the primary particle crystal structure can be reduced, thereby preventing and / or slowing down the generation of cracks caused by strain caused by the random volume contraction / expansion of the primary particles during charging and discharging.

[0028] As defined herein, when the positive electrode active material is charged to 4.3 V, the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the primary particle crystal structure may be less than 0.019.

[0029] By making the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the above-mentioned primary particles present in the above-mentioned secondary particles less than 0.019nm, the crystal defects (especially line defects) in the crystal structure of the primary particles constituting the above-mentioned lithium composite oxide are reduced, thereby preventing and / or mitigating the generation of cracks caused by strain caused by random volume shrinkage / expansion of the primary particles during charging and discharging.

[0030] The grain size of the positive electrode active material may be 70 nm to 130 nm.

[0031] By using a dopant that hinders the growth of primary particles during the calcination process of the above-mentioned positive electrode active material and increasing the calcination temperature, the excessive growth of primary particles is suppressed and the crystallinity of the primary particles is improved, so that the above-mentioned positive electrode active material can have a grain size of 70nm to 135nm.

[0032] The secondary particles may be represented by the following Chemical Formula 1.

[0033] [Chemical formula 1]

[0034] Li a Ni 1-(b+c+d) Co b M1 c M2 d O2

[0035] Among them, M1 is at least one selected from Mn and Al, M2 is at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, M1 and M2 are different from each other, 0.5≤a≤1.5, 0≤b≤0.20, 0≤c≤0.30, 0≤d≤0.10.

[0036] In the secondary particles, the molar fraction of nickel relative to all elements except lithium may be 70% or more.

[0037] Furthermore, according to another aspect of the present invention, a positive electrode including the positive electrode active material is provided.

[0038] In addition, according to another aspect of the present invention, a lithium secondary battery using the positive electrode is provided.

[0039] Effects of the Invention

[0040] According to the present invention, during the calcination process of the positive electrode active material, a dopant that hinders the growth of primary particles constituting the lithium composite oxide is used, and the calcination temperature is increased, thereby suppressing the excessive growth of the primary particles and improving the crystallinity of the primary particles. This prevents and / or slows down the generation of gas and swelling in the lithium secondary battery caused by the above-mentioned positive electrode active material while maintaining the electrochemical properties of the lithium secondary battery using the above-mentioned lithium composite oxide as the positive electrode active material.

[0041] In addition, the present invention reduces crystal defects in the crystal structure of primary particles constituting the lithium composite oxide, thereby preventing and / or alleviating crack generation caused by strain due to random volume contraction / expansion of the primary particles during charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a cross-sectional SEM image of the positive electrode active material according to Example 1 charged to 4.3V.

[0043] Figure 2 This is a cross-sectional SEM image of the positive electrode active material according to Comparative Example 1 charged to 4.3V.

[0044] Figure 3 This is a cross-sectional SEM image of the positive electrode active material according to Comparative Example 2 charged to 4.3 V.

[0045] Figure 4 This is a cross-sectional SEM image of the positive electrode active material according to Comparative Example 4 charged to 4.3 V.

[0046] Figure 5 This is a cross-sectional SEM image of the positive electrode active material according to Comparative Example 5 charged to 4.3 V. DETAILED DESCRIPTION

[0047] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.

[0048] Positive active material

[0049] According to one aspect of the present invention, the positive electrode active material includes primary particles capable of lithium insertion / extraction and secondary particles formed by agglomerating the primary particles. For convenience, the primary particles and / or the secondary particles may be referred to as lithium composite oxides herein.

[0050] The lithium composite oxide is a composite metal oxide capable of inserting and extracting lithium ions and has a layered crystal structure belonging to the R-3m space group. The lithium composite oxide having a layered crystal structure exhibits a characteristic peak in the region of 2θ of 18° to 20° in the diffraction pattern obtained by XRD analysis.

[0051] The lithium composite oxide may include at least one selected from nickel, cobalt, manganese, and aluminum.

[0052] Preferably, the lithium composite oxide may be a lithium nickel-based composite oxide containing nickel.

[0053] In one embodiment, LiNiO2 can be a ternary type lithium composite oxide such as NCM (Ni-Co-Mn) and NCA (Ni-Co-Al) or a quaternary type lithium composite oxide such as NCMA (Ni-Co-Mn-Al) in which a portion of nickel is replaced by cobalt, manganese and / or aluminum in order to improve low rate performance and life performance while maintaining high reversible capacity. In another embodiment, the lithium nickel-based composite oxide can be a cobalt-free lithium composite oxide.

[0054] The primary particles constituting the secondary particles may have a rod (rod) shape, an elliptical shape and / or an irregular shape. In addition, unless specifically designed in the preparation process, primary particles of various shapes may exist in the same positive electrode active material. In addition, the primary particles refer to particle units that do not appear to have grain boundaries when observed with a scanning electron microscope at a magnification of 5000 to 20000 times.

[0055] The average particle size of the primary particles constituting the lithium composite oxide defined herein may be 0.04 μm to 2 μm, 0.06 μm to 2 μm, 0.08 μm to 2 μm, 0.1 μm to 2 μm, 0.25 μm to 2 μm, 0.04 μm to 1 μm, 0.06 μm to 1.0 μm, 0.08 μm to 1 μm, 0.1 μm to 1 μm, 0.25 μm to 1 μm, 0.04 μm to 0.75 μm, 0.06 μm to 0.75 μm, 0.08 μm to 0.75 μm, 0.1 μm to 0.75 μm or 0.25 μm to 0.75 μm. At this time, as the average particle size of the primary particles, the average value of the length in the major axis direction and the length in the minor axis direction of the primary particles ([major axis length + minor axis length] / 2) may be used.

[0056] The primary particles may be composed of a single crystal grain or a plurality of crystal grains. In this case, the size of the crystal grains may be calculated from XRD analysis of the positive electrode active material.

[0057] For example, the above-mentioned grain size can be calculated by the following methods: ① using all peaks present in the diffraction pattern obtained from the XRD analysis to calculate (using pattern fitting, Rietveld refinement method) or ② substituting the half-maximum full width of a specific peak present in the diffraction pattern obtained from the XRD analysis (for example, a characteristic peak of a crystal plane corresponding to the (003) plane, etc.) into the Scherrer equation for calculation.

[0058] The crystallite size present in the above-mentioned lithium composite oxide is preferably 70nm to 130nm. In addition, the crystallite size present in the above-mentioned lithium composite oxide is preferably 70nm to 120nm, 70nm to 110nm, 70nm to 105nm, 70nm to 103nm, 75nm to 120nm, 75nm to 110nm, 75nm to 105nm, 75nm to 103nm, 80nm to 120nm, 80nm to 110nm, 80nm to 105nm, 80nm to 103nm, 85nm to 120nm, 85nm to 110nm, 85nm to 105nm, 85nm to 103nm, 90nm to 120nm, 90nm to 110nm, 90nm to 105nm or 90nm to 103nm. When the crystal size is less than 70 nm, the crystal size constituting the positive electrode active material is too small, so the particle strength of the lithium composite oxide may be reduced. In addition, as the crystal size and the size of the primary particles are excessively reduced, the specific surface area may increase, thereby promoting gas generation due to a side reaction with the electrolyte.

[0059] On the other hand, when the crystal grain size is greater than 130 nm, the primary particles grow excessively, and thus electrochemical performance such as rate performance of a lithium secondary battery using the crystal grain as a positive electrode active material may be reduced.

[0060] As described below, according to the present invention, by using an impurity that hinders the growth of primary particles during the calcination process of the above-mentioned positive electrode active material and increasing the calcination temperature, the excessive growth of primary particles is suppressed and the crystallinity of the primary particles is improved, so that the above-mentioned positive electrode active material can have a grain size of 70nm to 130nm.

[0061] As described above, during the calcination process of the above-mentioned positive electrode active material, as a dopant that hinders the growth of primary particles, at least one selected from Al2O3, Al(OH)3, AlPO4, Al(PO3)3, WO3, Nb2O5, TiO2, H3BO3, H2B4O7, B2O3, B2O5, C6H5B(OH)2, (C6H5O)3B, [(CH3(CH2)3O)3B, C3H9B3O6 and (C3H7O3)B can be used.

[0062] If the calcination temperature is increased (i.e., over-calcination) during the calcination of the positive electrode active material without using a dopant that hinders the growth of primary particles, the grains and primary particles may grow excessively. In this case, a phase change (e.g., layered structure → rock salt structure) may occur on the surface of the primary particles and the secondary particles due to cation mixing. Such changes in crystal structure such as phase change may cause changes in the surface resistance of the positive electrode active material and deterioration of its life.

[0063] On the other hand, if the calcination temperature of the positive electrode active material is kept constant and a dopant that hinders the growth of primary particles is used during the calcination process, the growth of the crystal grains and the primary particles may be excessively inhibited. In this case, as the size of the crystal grains and the size of the primary particles are excessively reduced, the specific surface area increases, which may promote gas generation due to a side reaction with the electrolyte.

[0064] The average particle size of the secondary particles may be 0.5 μm to 20 μm, 2.0 μm to 18 μm, 2.0 μm to 15 μm or 3.0 μm to 12 μm. In addition, when the secondary particles are small particles, the average particle size of the secondary particles may be 7 μm or less, 6.5 μm or less, 6 μm or less, 5.5 μm or less, 5 μm or less, 4.5 μm or less, 4 μm or less, 3.5 μm or less or 3 μm or less, and may be 0.5 μm or more, 1 μm or more, 1.5 μm or more or 2 μm or more. When the secondary particles are small particles, the upper and lower limits of the average particle size of the secondary particles may be appropriately selected within the range that satisfies the above definition. When the secondary particles are large particles, the average particle size of the secondary particles may be greater than 7 μm, greater than or equal to 7.5 μm, greater than or equal to 8 μm, greater than or equal to 8.5 μm, greater than or equal to 9 μm, greater than or equal to 9.5 μm, greater than or equal to 10 μm, greater than or equal to 10.5 μm, greater than or equal to 11 μm, greater than or equal to 11.5 μm or greater than or equal to 12 μm, and may be less than or equal to 30 μm, less than or equal to 27.5 μm, less than or equal to 25 μm, less than or equal to 22.5 μm, less than or equal to 20 μm, less than or equal to 17.5 μm or less than or equal to 15 μm. When the secondary particles are large particles, the upper and lower limits of the average particle size of the secondary particles may be appropriately selected within the range that satisfies the above definition. When the positive electrode active material has a bimodal particle size distribution including secondary particles as small particles and secondary particles as large particles, the average particle size of the positive electrode active material may be 4 μm to 18 μm, 6 μm to 16 μm, or 8 μm to 14 μm.

[0065] The average particle size of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles. The average particle size (D50) of the secondary particles may be measured using a laser diffraction method. For example, after the secondary particles are dispersed in a dispersion medium, they are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiated with ultrasonic waves of about 28kHz at a power of 60W, and then the volume cumulative particle size distribution diagram is obtained, and the particle size equivalent to 50% of the volume cumulative amount is obtained to achieve measurement. In addition, in other cases, the average particle size of the secondary particles may be calculated as the average value of the particle size of the secondary particles confirmed by the SEM image.

[0066] According to the present invention, by using dopants that hinder the growth of primary particles and increasing the calcination temperature, the excessive growth of primary particles can be suppressed, and at the same time, the crystallinity of the primary particles can be improved, thereby reducing crystal defects in the crystal structure of the primary particles, and preventing and / or alleviating crack generation caused by strain caused by random volume shrinkage / expansion of primary particles during charging and discharging.

[0067] The crystal defects in the crystal structure of the primary particle may include point defects and / or line defects, but according to the present invention, in particular, the line defects in the crystal structure of the primary particle can be reduced. The line defects may exist in the form of extending in a direction parallel to the (003) plane in the crystal structure of the primary particle.

[0068] As described above, when there are line defects in the direction parallel to the (003) plane in the crystal structure of the primary particles, cracks may be generated inside the primary particles along the line defects as strains are accumulated due to random volume contraction / expansion of the primary particles during charge and discharge. At this time, the cracks caused by the line defects in the primary particles are different from the cracks generated along the grain boundaries of adjacent primary particles due to the accumulation of strains caused by random volume contraction / expansion of the primary particles during charge and discharge.

[0069] Line defects present in the crystal structure of the primary particles may be caused by dislocation of the layered crystal structure within the primary particles. When the layered crystal structure within the primary particles is dislocated, the interplanar distances between some crystal planes may change. The change in interplanar distance can be detected by XRD analysis of the positive active material using Cu-Kα line or other known methods.

[0070] For example, for the above-mentioned positive electrode active material after charging under predetermined conditions, if the (003) plane-specific diffraction peak (2θ=18°~20°) appears split in the diffraction pattern obtained by XRD analysis using Cu-Kα lines, it can be predicted that crystal defects have occurred on the (003) plane in the above-mentioned primary particle.

[0071] Therefore, the change in interplanar spacing can be quantified by substituting the 2θ difference between the two peaks split in the 2θ region of 18° to 20° into Bragg's law (interplanar spacing (d) = λ / 2sinθ). In addition, another method is to obtain a TEM image (e.g., HAADF-STEM) fitted with the (003) plane from the cross section of the above primary particle and then measure the distance between adjacent (003) planes.

[0072] At this time, the charging conditions of the positive electrode active material before XRD analysis can be general formation and / or charging conditions of lithium secondary batteries. For example, the positive electrode active material can be charged to 4.3V before XRD analysis.

[0073] More specifically, a lithium secondary battery (half-cell) using the above-mentioned positive electrode active material as the positive electrode and lithium foil as the negative electrode is charged and discharged twice at 25°C, a voltage range of 3.0V to 4.3V and 0.05C / 0.05C, and then charged to 4.3V again. The above-mentioned positive electrode active material can be recovered from the above-mentioned half-cell and subjected to XRD analysis.

[0074] As described above, when the above-mentioned positive electrode active material charged to 4.3V is subjected to XRD analysis, no peak splitting occurs in the region where 2θ is 18° to 20°, or, if there is peak splitting, the 2θ difference between the two split peaks is preferably less than 0.75°, less than 0.70°, less than 0.69° or less than 0.681°.

[0075] As described above, the maximum value (d1) and / or minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the primary particle may vary slightly depending on the charge state of the positive electrode active material and the composition of the positive electrode active material (e.g., the molar fraction of nickel).

[0076] However, the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the above-mentioned primary particle is not significantly affected by the charging state of the above-mentioned positive electrode active material or the change in the molar fraction of nickel in the above-mentioned positive electrode active material, and therefore can be used as an indicator of crystal defects in the crystal structure of the primary particle.

[0077] Therefore, the smaller the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the above-mentioned primary particle crystal structure, the more the crystal defects in the primary particle crystal structure can be reduced, thereby preventing and / or slowing down the generation of cracks caused by strain caused by the random volume contraction / expansion of the primary particles during charging and discharging.

[0078] For example, in the above-mentioned positive electrode active material, the molar fraction of nickel relative to all elements except lithium can be greater than 70%, and when the above-mentioned positive electrode active material is charged to 4.3V, the maximum value (d1) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the above-mentioned primary particles present in the above-mentioned secondary particles can be less than 0.4794nm, less than 0.4789nm, less than 0.478nm or less than 0.4775nm, and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the above-mentioned primary particles present in the above-mentioned secondary particles can be greater than 0.456nm, greater than 0.457nm, greater than 0.458nm, greater than 0.459nm or greater than 0.4598nm.

[0079] If the maximum value (d1) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the above-mentioned primary particle present in the above-mentioned secondary particle is greater than 0.4794nm, the interplanar spacing of another (003) plane adjacent to the above-mentioned (003) plane may become too narrow. In addition, if the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the above-mentioned primary particle present in the above-mentioned secondary particle is less than 0.456nm, the interplanar spacing of another (003) plane adjacent to the above-mentioned (003) plane may become too wide. Therefore, the interplanar spacing between adjacent (003) planes is unbalanced, so that linear defects exist in the crystal structure of the above-mentioned primary particle along a direction parallel to the (003) plane.

[0080] As defined herein, when the above-mentioned positive electrode active material is charged to 4.3V, the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) planes in the crystal structure of the above-mentioned primary particles present in the above-mentioned secondary particles may be less than 0.019nm, less than or equal to 0.018nm, less than or equal to 0.0175nm, or less than or equal to 0.0172nm.

[0081] By making the difference (Δd) between the maximum value (d1) and the minimum value (d2) of the interplanar spacing (d-spacing) of the (003) plane in the crystal structure of the above-mentioned primary particles present in the above-mentioned secondary particles less than 0.019nm, the crystal defects (especially line defects) in the crystal structure of the primary particles constituting the above-mentioned lithium composite oxide are reduced, thereby preventing and / or mitigating the generation of cracks caused by strain caused by random volume shrinkage / expansion of the primary particles during charging and discharging.

[0082] The lithium composite oxide (primary particles and secondary particles) defined herein may be represented by Chemical Formula 1 below.

[0083] [Chemical formula 1]

[0084] Li a Ni 1-(b+c+d) Co b M1 c M2 d O2

[0085] Among them, M1 is at least one selected from Mn and Al, M2 is at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, M1 and M2 are different from each other, 0.5≤a≤1.5, 0≤b≤0.20, 0≤c≤0.30, 0≤d≤0.10.

[0086] a, which represents the ratio of lithium to all elements except lithium in the lithium composite oxide, may be 0.5 to 1.5, 0.75 to 1.25, 0.90 to 1.1, or 0.95 to 1.05.

[0087] In one embodiment, the molar fraction of nickel relative to all elements except lithium in the lithium composite oxide may be 70% or more. In this case, in the chemical formula 1, b+c+d is 0.30 or less.

[0088] In addition, according to another embodiment, the molar fraction of nickel relative to all elements except lithium in the above-mentioned lithium composite oxide can be greater than 75% (in this case, b+c+d is less than 0.25), greater than 80% (in this case, b+c+d is less than 0.20), greater than 85% (in this case, b+c+d is less than 0.15), or greater than 90% (in this case, b+c+d is less than 0.10).

[0089] When the lithium composite oxide contains cobalt, the molar fraction of cobalt relative to all elements other than lithium in the secondary particles may be 20% or less (in this case, b is 0.20 or less), 15% or less (in this case, b is 0.15 or less), 10% or less (in this case, b is 0.10 or less), or 5% or less (in this case, b is 0.05 or less). When the secondary particles contain cobalt, b in the chemical formula 1 is greater than 0.

[0090] When the lithium composite oxide contains manganese and / or aluminum, the molar fraction of manganese and / or aluminum relative to all elements other than lithium in the lithium composite oxide may be 30% or less (in this case, c is 0.30 or less), 25% or less (in this case, c is 0.25 or less), 20% or less (in this case, c is 0.20 or less), 15% or less (in this case, c is 0.15 or less), 10% (in this case, c is 0.10 or less), or 5% or less (in this case, c is 0.05 or less). When the secondary particles contain manganese and / or aluminum, c in the chemical formula 1 is greater than 0.

[0091] In the above chemical formula 1, M2 refers to a dopant present in the above secondary particles. The above dopant may be present in the lattice of the above primary particles in a doped state. In addition, in the above chemical formula 1, M2 may optionally include a dopant for hindering the growth of the primary particles during the calcination of the above positive active material. In addition, when the above dopant is doped, the electrochemical properties of the above positive active material can be improved.

[0092] When the secondary particle contains a dopant, M2 in the chemical formula 1 is greater than 0. Furthermore, the molar fraction of the dopant relative to all elements other than lithium in the secondary particle may be 10% or less (in this case, d is 0.10 or less), 5% or less (in this case, d is 0.05 or less), 4% or less (in this case, d is 0.04 or less), 3% or less (in this case, d is 0.03 or less), 2% or less (in this case, d is 0.02 or less), 1% or less (in this case, d is 0.01 or less), 0.5% or less (in this case, d is 0.005 or less), 0.4% or less (in this case, d is 0.004 or less), 0.3% or less (in this case, d is 0.003 or less), 0.2% or less (in this case, d is 0.002 or less), or 0.1% or less (in this case, d is 0.001 or less).

[0093] When the secondary particles selectively contain a dopant, the dopant may include at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, or at least one selected from B, Al, Nb and W. The type and combination of the dopant may be appropriately selected within the range that does not negatively affect the electrochemical performance and stability of the positive electrode active material.

[0094] Lithium secondary battery

[0095] According to another aspect of the present invention, a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector may be provided. The positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, the positive electrode active material is the same as that described previously, so for convenience, its specific description is omitted, and only the remaining structures not described above are described below.

[0096] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.

[0097] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.

[0098] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.

[0099] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.

[0100] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.

[0101] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.

[0102] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.

[0103] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.

[0104] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.

[0105] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.

[0106] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.

[0107] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0108] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.

[0109] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.

[0110] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; such as SiO β(0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, a metal oxide capable of being doped and dedoped with lithium; or a composite containing the above metal compound and a carbon material such as a Si-C composite or a Sn-C composite, etc., one or a mixture of two or more of them can be used. In addition, as the above negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, kishgraphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesophase carbon microbeads, mesophase pitch, and high-temperature calcined carbons such as petroleum or coal tar pitch derived cokes.

[0111] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.

[0112] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.

[0113] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.

[0114] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.

[0115] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.

[0116] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.

[0117] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0118] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.

[0119] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.

[0120] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.

[0121] As the material of the sulfide solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In) and S can be used. Examples of the above-mentioned sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are integers, Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.

[0122] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, a crystalline state, or a mixed state of the amorphous state and the crystalline state.

[0123] Examples of materials for oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x Ln3Z1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li 3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO4(LISICON), etc.

[0124] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.

[0125] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0126] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).

[0127] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.

[0128] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.

[0129] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.

[0130] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.

[0131] Preparation Example 1. Preparation of positive electrode active material

[0132] Example 1

[0133] Spherical Ni was synthesized using the co-precipitation method. 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Specifically, 50 wt% NaOH and 18 wt% NH4OH are added to a 1.5M composite transition metal sulfuric acid aqueous solution prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 90:5:5 in a 90L reactor. The pH is maintained at 12.0 in the reactor. At this time, the reactor temperature is maintained at 45°C, and N2 as an inert gas is added to the reactor to prevent the prepared precursor from being oxidized. After the synthesis stirring is completed, a filter press (Filter press, F / P) device is used for washing and dehydration to obtain Ni 0.90 Co 0.05 Mn 0.05(OH)2 hydroxide precursor. Then, the hydroxide precursor, LiOH (Li / (Ni+Co+Mn) molar ratio is 1.01) and H3BO3 (weighed so that the molar fraction of boron in the metal element is 0.01 based on the overall composition of the hydroxide precursor) are mixed, heat treated at 700°C in an O2 atmosphere for 12 hours, and then vacuum dried at 120°C and washed with water to obtain a positive electrode active material.

[0134] Example 2

[0135] Spherical Ni was synthesized by coprecipitation method 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Specifically, 50 wt% NaOH and 18 wt% NH4OH are added to a 1.5M composite transition metal sulfuric acid aqueous solution prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 90:5:5 in a 90L reactor. The pH is maintained at 12.0 in the reactor. At this time, the reactor temperature is maintained at 45°C, and N2 as an inert gas is added to the reactor to prevent the prepared precursor from being oxidized. After the synthesis stirring is completed, a filter press (Filter press, F / P) device is used for washing and dehydration to obtain Ni 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Then, the hydroxide precursor, LiOH (Li / (Ni+Co+Mn) molar ratio is 1.01) and WO3 (weighed so that the molar fraction of tungsten in the metal element is 0.005 based on the overall composition of the hydroxide precursor) are mixed, heat treated at 700°C in an O2 atmosphere for 12 hours, and then vacuum dried at 120°C and washed with water to obtain a positive electrode active material.

[0136] Comparative Example 1

[0137] Spherical Ni was synthesized by coprecipitation 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Specifically, 50 wt% NaOH and 30 wt% NH4OH are added to a 1.5M composite transition metal sulfuric acid aqueous solution prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 90:5:5 in a 90L reactor. The pH is maintained at 11.5 in the reactor. At this time, the reactor temperature is maintained at 60°C, and N2 as an inert gas is added to the reactor to prevent the prepared precursor from being oxidized. After the synthesis stirring is completed, a filter press (Filter press, F / P) device is used for washing and dehydration to obtain Ni 0.90 Co0.05 Mn 0.05 Next, the hydroxide precursor was mixed with LiOH (Li / (Ni+Co+Mn) molar ratio = 1.01), heat treated at 670°C in an O2 atmosphere for 12 hours, and then vacuum dried at 120°C and washed with water to obtain a positive electrode active material.

[0138] Comparative Example 2

[0139] Spherical Ni was synthesized by coprecipitation 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Specifically, 50 wt% NaOH and 30 wt% NH4OH are added to a 1.5M composite transition metal sulfuric acid aqueous solution prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 90:5:5 in a 90L reactor. The pH is maintained at 11.5 in the reactor. At this time, the reactor temperature is maintained at 60°C, and N2 as an inert gas is added to the reactor to prevent the prepared precursor from being oxidized. After the synthesis stirring is completed, a filter press (Filter press, F / P) device is used for washing and dehydration to obtain Ni 0.90 Co 0.05 Mn 0.05 Next, the hydroxide precursor was mixed with LiOH (Li / (Ni+Co+Mn) molar ratio = 1.01), heat treated at 700°C for 12 hours in an O2 atmosphere, and then vacuum dried at 120°C and washed with water to obtain a positive electrode active material.

[0140] Comparative Example 3

[0141] A positive electrode active material was prepared in the same manner as in Example 1 except that H 3 BO 3 was used so that the molar fraction of boron in the metal element was 0.015 based on the overall composition of the hydroxide precursor.

[0142] Comparative Example 4

[0143] Spherical Ni was synthesized by coprecipitation 0.90 Co 0.05 Mn 0.05(OH)2 hydroxide precursor. Specifically, 50 wt% NaOH and 30 wt% NH4OH are added to a 1.5M composite transition metal sulfuric acid aqueous solution prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 90:5:5 in a 90L reactor. The pH is maintained at 11.5 in the reactor. At this time, the reactor temperature is maintained at 60°C, and N2 as an inert gas is added to the reactor to prevent the prepared precursor from being oxidized. After the synthesis stirring is completed, a filter press (Filter press, F / P) device is used for washing and dehydration to obtain Ni 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Then, the hydroxide precursor, LiOH (Li / (Ni+Co+Mn) molar ratio = 1.01) and H3BO3 (weighed so that the molar fraction of boron in the metal element is 0.02 based on the overall composition of the hydroxide precursor) are mixed, heat treated at 700°C in an O2 atmosphere for 12 hours, then vacuum dried at 120°C, and washed with water to obtain a positive electrode active material.

[0144] Comparative Example 5

[0145] Spherical Ni was synthesized by coprecipitation 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Specifically, 50 wt% NaOH and 30 wt% NH4OH are added to a 1.5M composite transition metal sulfuric acid aqueous solution prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 90:5:5 in a 90L reactor. The pH is maintained at 11.5 in the reactor. At this time, the reactor temperature is maintained at 60°C, and N2 as an inert gas is added to the reactor to prevent the prepared precursor from being oxidized. After the synthesis stirring is completed, a filter press (Filter press, F / P) device is used for washing and dehydration to obtain Ni 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Then, the hydroxide precursor, LiOH (Li / (Ni+Co+Mn) molar ratio = 1.01) and H3BO3 (weighed so that the molar fraction of boron in the metal element is 0.01 based on the overall composition of the hydroxide precursor) are mixed, heat treated at 670°C in an O2 atmosphere for 12 hours, then vacuum dried at 120°C, and washed with water to obtain a positive electrode active material.

[0146] Comparative Example 6

[0147] Spherical Ni was synthesized by coprecipitation0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor. Specifically, 50 wt% NaOH and 30 wt% NH4OH are added to a 1.5M composite transition metal sulfuric acid aqueous solution prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 90:5:5 in a 90L reactor. The pH is maintained at 11.5 in the reactor. At this time, the reactor temperature is maintained at 60°C, and N2 as an inert gas is added to the reactor to prevent the prepared precursor from being oxidized. After the synthesis stirring is completed, a filter press (Filter press, F / P) device is used for washing and dehydration to obtain Ni 0.90 Co 0.05 Mn 0.05 (OH)2 hydroxide precursor.

[0148] Next, the above-mentioned hydroxide precursor, LiOH (Li / (Ni+Co+Mn) molar ratio = 1.01) and H3BO3 (weighed so that the molar fraction of boron in the metal element is 0.01 based on the overall composition of the above-mentioned hydroxide precursor) are mixed, heat treated in an O2 atmosphere at 730°C for 12 hours, and then vacuum dried at 120°C and washed with water to obtain a positive electrode active material.

[0149] Preparation Example 2. Fabrication of a lithium secondary battery (half-cell)

[0150] 94 wt % of each positive electrode active material prepared according to Preparation Example 1, 3 wt % of carbon black and 3 wt % of PVDF binder were dispersed in 30 g of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum film having a thickness of 15 μm and vacuum dried at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0151] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7 is used to prepare a half-cell.

[0152] Preparation Example 3. Preparation of lithium secondary battery (full battery)

[0153] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 4.5 wt % of carbon black, and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry.

[0154] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.

[0155] Relative to the above-mentioned positive electrode, a graphite electrode is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 20 μm) is used as a separation membrane, and a full battery is prepared using an electrolyte solution in which LiPF6 is present at a concentration of 1.15 M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4.

[0156] Experimental Example 1. XRD analysis of positive electrode active material

[0157] X-ray diffraction (XRD) analysis was performed to measure the crystallite size and the interplanar spacing of the (003) plane of the positive electrode active material. The XRD analysis was performed using a Bruker D8 ENDEAVOR diffractometer.

[0158] Specifically, the diffraction pattern obtained by XRD analysis of each positive electrode active material prepared according to Preparation Example 1 was subjected to Rietveld refinement using TOPAS software, and the Lvol-IB value was calculated as the grain size of the positive electrode active material.

[0159] In addition, the lithium secondary battery (half-cell) prepared according to Preparation Example 2 was subjected to two charge and discharge cycles at 25°C, a voltage range of 3.0V to 4.3V and 0.05C / 0.05C using an electrochemical analyzer (Toyo, Toscat-3100), and then charged to 4.3V again. The positive electrode active material was then recovered from the half-cell and subjected to XRD analysis. The degree of peak splitting in the 2θ region of 18° to 20° and the maximum (d1) and minimum (d2) values ​​of the interplanar spacing (d-spacing) of the (003) plane were calculated from the diffraction peak attributed to the (003) plane.

[0160] The above XRD analysis results are shown in Table 1 below.

[0161] Table 1

[0162]

[0163]

[0164] *Peak splitting refers to the 2θ difference between two peaks split in the region of 18° to 20° 2θ.

[0165] In addition, referring to the cross-sectional SEM images of the positive electrode active materials (Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 4 and Comparative Example 5) recovered from the half-cells, Figures 1 to 5 It can be confirmed that, compared with the positive electrode active material according to Example 1, the positive electrode active materials according to Comparative Examples 1, 2, 4 and 5 have more line defects in the primary particles.

[0166] Experimental Example 2. Evaluation of electrochemical performance of lithium secondary battery (half-cell)

[0167] The lithium secondary battery (half-cell) prepared according to Preparation Example 2 was subjected to a charge / discharge experiment using an electrochemical analyzer (Toyo, Toscat-3100) at 25°C, a voltage range of 3.0 V to 4.3 V, and a discharge rate of 1.0 C to 0.1 C to determine the initial charge capacity, initial discharge capacity, initial efficiency, and 1.0 C / 0.1 C rate performance.

[0168] In addition, using an electrochemical analyzer (Toyo, Toscat-3100), charge / discharge was performed 100 times at 25° C., a voltage range of 3.0 V to 4.3 V, and 1C / 1C, and then the ratio of the discharge capacity at the 100th cycle (cycle capacity retention) was measured.

[0169] The above measurement results are shown in Table 2 below.

[0170] Table 2

[0171]

[0172] It can be confirmed from the grain size in Table 1 that the positive electrode active material according to Examples 1 and 2 uses a dopant that hinders the growth of primary particles constituting the lithium composite oxide during the calcination process and increases the calcination temperature, thereby suppressing the excessive growth of primary particles and improving the crystallinity of the primary particles. This reduces the crystal defects in the crystal structure of the primary particles constituting the above-mentioned lithium composite oxide while maintaining the electrochemical properties such as the initial efficiency and rate performance of the lithium secondary battery using the above-mentioned lithium composite oxide as the positive electrode active material, thereby improving the life performance.

[0173] Experimental Example 3. Volume change measurement of lithium secondary battery (half-cell)

[0174] The lithium secondary battery (full battery) prepared according to Preparation Example 3 was subjected to a formation process of 3 cycles at 25°C, a voltage range of 2.75V to 4.3V, and 0.2C / 0.2C using an electrochemical analysis device (Toyo, Toscat-3100). Next, the positive electrode charged at 4.3V was recovered from the full battery, and a new soft-pack battery injected with an electrolyte was manufactured. While each soft-pack battery was stored at 70°C, and after 14 and 28 days, an electron density meter (SID-220W) was used to measure the volume change relative to the initial soft-pack battery volume.

[0175] The above measurement results are shown in Table 3 below.

[0176] Table 3

[0177]

[0178] Referring to the results in Table 3 above, it can be confirmed that in a full battery using a positive electrode active material having a similar grain size, the volume growth rate of the full battery using the positive electrode active material according to Examples 1 and 2 is lower than the volume growth rate of the full battery using the positive electrode active material according to Comparison Examples 1, 3, 4 and 5.

[0179] In other words, the positive electrode active material according to the present invention suppresses the excessive growth of primary particles and improves the crystallinity of primary particles, so that compared with lithium secondary batteries using other positive electrode active materials with similar particle sizes, it has the advantage of preventing and / or reducing gas generation and swelling phenomena in lithium secondary batteries.

[0180] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of ​​the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.

Claims

1. A positive electrode active material comprising primary particles capable of inserting or removing lithium ions and secondary particles formed by agglomerating the primary particles, wherein the positive electrode active material is characterized in that: The secondary particles include at least one selected from nickel, cobalt, manganese and aluminum. Based on the half-cell, when charged to 4.3 V, the difference Δd between the maximum value d1 and the minimum value d2 of the interplanar spacing, ie, the d-spacing, of the (003) planes within the primary particle is less than 0.019 nm.

2. The positive electrode active material according to claim 1, characterized in that The maximum value d1 of the interplanar spacing, ie, the d-spacing, of the (003) planes in the crystal structure of the primary particles present in the secondary particles is less than 0.4794 nm.

3. The positive electrode active material according to claim 1, characterized in that The minimum value d2 of the interplanar spacing, ie, the d-spacing, of the (003) planes in the crystal structure of the primary particles present in the secondary particles is 0.461 nm or more.

4. The positive electrode active material according to claim 1, characterized in that The grain size of the positive electrode active material is 70 nm to 130 nm.

5. The positive electrode active material according to claim 1, characterized in that The secondary particles are represented by the following chemical formula 1: [Chemical formula 1] The a Nor 1-(b+c+d) Co b M1 c M2 d O2 (in, M1 is at least one selected from Mn and Al, M2 is at least one selected from Na, K, Mg, Ca, Ba, Mn, B, Ce, Hf, Ta, Cr, F, Al, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, Ge, Nd, Gd and Cu, M1 and M2 are different from each other. 0.5≤a≤1.5, 0≤b≤0.20, 0≤c≤0.30, 0≤d≤0.10).

6. The positive electrode active material according to claim 5, characterized in that In the secondary particles, the molar fraction of nickel relative to all elements except lithium is 70% or more.

7. The positive electrode active material according to claim 5, characterized in that The M2 mentioned above includes at least one selected from B, Al, Nb and W.

8. The positive electrode active material according to claim 1, characterized in that In the XRD analysis of the positive electrode active material, no peak splitting occurs in the region where 2θ is 18° to 20°.

9. The positive electrode active material according to claim 1, characterized in that In an XRD analysis of the positive electrode active material, the difference in 2θ between two split peaks in a region where 2θ is 18° to 20° is 0.75° or less.

10. A positive electrode, characterized in that: The invention comprises a positive electrode active material prepared by the preparation method according to any one of claims 1 to 9.

11. A lithium secondary battery, characterized in that: The positive electrode according to claim 10 is used.